A Study of the Changes in Time Implications in the Translation of Safi Najafi from Khayyam's Quatrains Relying on Cohesive Devices of the Text - Fereshte Naseri (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2019)
According to some critics and literates, the translation of the contemporary Iraqi poet, Ahmad Safi Najafi from Khayyam's quatrains is at a high level of poetry and beauty. Apart from the positive features of this translation, we witness some changes in the discourse and the implications of Khayyam poetry in the quatrains’ translation. The present paper seeks to analyze the translation based on the cohesion principle and cohesive devices of the text, which was proposed by Michael Halliday and Ruqaiya Hasan, and to observe the changes that have been made in the Khayyam's temporal discourse and the time element in the quatrains, observing, and it can point to the importance of the imperious and form relations of the text in the translation so. According to the analyses carried out, lack of attention to the cohesive devices such as conjunctions (casual and temporal conjunctions) and lexical factors and eliminations in the translation process has caused the collapse of multiple time implications in the Khayyam quatrains’.